iGeneration’s Communication Psychology Facing Covid-19 In Terms of Cognitive Dissonance - Dianingtyas Putri; Suharyanti Suharyanti; Dyah Ajeng (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
The Covid-19 pandemic has a broad impact on various aspects and lines. One of them is that the country’s economy has not moved forward as before. The unemployment rate increase among the iGeneration who have just graduated from college feels confused and anxious because they have not found a job, thus negatively affected them. This research aims to analyze the iGeneration in facing the impact of Covid-19 pandemic in cognitive dissonance theory by linking interpersonal communication through communication psychology. This research was a case study of a conservative generation of 22 years of age with excellent academic achievements. The results show that of the three mental mechanisms that consist of selective prevents dissonance, post-decision dissonance creates a need for reassurance, and minimal justification for action induces a shift in attitude, the informants have different perspectives and perceptions that affect self-efficacy on the issue as cognitive dissonance.